Ion Track Etching Revisited: IV. Thermal annealing of fresh swift heavy ion-irradiated PET in different environments. Issue 1 (1st February 2021) - Vacik, J.; Hnatowicz, V.; Kiv, A.; Fink, D.
ABSTRACT: Many studies have already been performed on the thermal annealing of fresh and aged swift heavy ion-irradiated polymers in a vacuum. In this paper we examine the influence of different environments on annealing behaviour. The basic tool for this study is current/voltage spectroscopy with the alternating voltage applied across the etched tracks. In previous work of this series it was shown for etching of previously annealed aged swift heavy ion-irradiated polyethylene terephthalate foils in dry air that at ∼ 50°C, a dip overlapped the expected Arrhenius correlation in the Arrhenius plot of the etchant breakthrough times. We had attributed that dip tentatively to the etching of the swift heavy ion track core material, as the latter had been subjected to extremely high radiation-damage and thus differs strongly in its composition from pristine bulk material. Repetition of this experiment under different annealing environments enables us to draw conclusions about the competition between the different polymeric disintegration and healing mechanisms in swift heavy ion tracks. These results should be useful for better estimation of the polymeric durability in different environments. First tests with polyimide reveals that a similar dip structure also shows up here, indicating that this finding may be a general effect for annealing of ion-irradiated polymers.